Բառապաշարի տարբեր շերտերի ոճական-երգիծական կիրառութիւնները Նշան Պեշիկթաշլեանի «Հիւանդտես» կատակերգութեան մէջ - Առաքելեան, Կարինէ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Армянская сатирическая литература имеет богатые традиции и глубокие корни. Сатирический жанр достиг своего апогея в XIX—XX вв., в частности, в творчестве западноармянских писателей Акопа Пароняна и Ерванда Отяна. Традиции западноармянской литературы переняли писатели диаспоры, в том числе Ншан Пешикташлян, более известный как сатирик. В комедии Ншана Пешикташляна «Посещение больного» изобилует словами, принадлежащими активным и неактивным слоям лексики, которые придают тексту особую стилистическую окрашенность и экспрессию. Эти слова также являются составной частью сатирической речи. The Armenian satirical literature has rich traditions and deep roots. The genre of satire reached its apogee in the 19th—20th centuries, in particular, in the works of Western Armenian writers Hagop Baronian and Yervant Odian. Being one of the most brilliant satirists in the Diaspora literature, Nshan Beshiktashlian followed the legacy of the Western Armenian writers. Nshan Beshiktashlian’s comedy «Visit to the Sick» is replete with words belonging to active and inactive layers of vocabulary, which give the text a special stylistic coloring and expression, and these words are also an integral part of satirical speech.
Keywords: Հայ գրականութիւն; Երգիծաբանութիւն